Seed germination and survival of the endangered psammophilous Rouya polygama (Apiaceae) in different light, temperature and NaCl conditions. Issue 4 (16th September 2014) - Santo, Andrea; Mattana, Efisio; Hugot, Laetitia; Spinosi, Paula; Bacchetta, Gianluigi
Abstract: Rouya polygama (Apiaceae) is an endangered Mediterranean species of great phytogeographical and ecological interest, growing on coastal sandy dunes. Intraspecific variability in the responses to constant temperatures (5–25°C) and an alternating temperature regime (25/10°C), salt stress (0–600 mM NaCl) and recovery of seed germination was evaluated among six populations from Sardinia and Corsica. Seeds were non-dormant and germination percentages ranged from 10 to 83%, depending on temperature and population. Differences in germination percentages were mainly due to different seed mortality among seed lots. R. polygama seeds germinated in salt concentrations up to 200 mM NaCl, whereas higher salt concentrations totally inhibited germination. Salt affected seed viability, and the recovery response decreased with increasing salinity and temperature. Inter-population variability and different sensitivity to NaCl in seed germination were detected. Our results are consistent with field germination in a period from autumn to spring, when water is available in the soil and temperatures are not prohibitive for seedling establishment, representing an advantageous ecological adaptation for seedling establishment to the unpredictable Mediterranean rainfall pattern. Further studies on R. polygama are needed to investigate germination requirements at temperatures higher than 25°C and its germination in the field, and to clarify genetic inter-population variability, considering a higher number of populations and possibly extending to North African populations.